2009
DOI: 10.4269/ajtmh.2009.81.489
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Interferon-Gamma and Interleukin-10 Responses to Plasmodium falciparum Liver Stage Antigen 1 and Thrombospondin-Related Adhesive Protein Immunodominant Epitopes in a Highland Population from Western Kenya

Abstract: Long-term planning to prevent malaria epidemics requires in-depth understanding of immunity to Plasmodium falciparum in areas of unstable transmission. Cytokine responses to immunodominant epitope peptides from liver stage antigen 1 (LSA-1) and thrombospondin-related adhesive protein (TRAP) were evaluated over a nine-month interval in adults and children in Kenya from a malaria epidemic–prone highland area after several years of low transmission. The proportion and magnitude of interferon-gamma ELISPOT respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
5
25
0
1
Order By: Relevance
“…Preimmunization IFN-␥ responses in malaria-experienced populations are important for establishing baseline values for subsequent vaccine trials, although as we have shown in this study that such responses vary greatly within and between individuals. Similar to our previous cross-sectional studies of pre-erythrocytic-stage malaria peptides (31,32), while an individual's responses varied between time points, the overall proportions of responders to each allele were similar across each season. Given the large proportion of adults responding to the 3D7 allele in this study, outcome measurements for an MSP1 vaccine tested in areas in which the disease is endemic may have to incorporate a fold increase over baseline and prolonged duration of immune response in order to distinguish between a vaccine-attributable affect and normal variation as the result of natural exposure.…”
Section: Downloaded Fromsupporting
confidence: 55%
“…Preimmunization IFN-␥ responses in malaria-experienced populations are important for establishing baseline values for subsequent vaccine trials, although as we have shown in this study that such responses vary greatly within and between individuals. Similar to our previous cross-sectional studies of pre-erythrocytic-stage malaria peptides (31,32), while an individual's responses varied between time points, the overall proportions of responders to each allele were similar across each season. Given the large proportion of adults responding to the 3D7 allele in this study, outcome measurements for an MSP1 vaccine tested in areas in which the disease is endemic may have to incorporate a fold increase over baseline and prolonged duration of immune response in order to distinguish between a vaccine-attributable affect and normal variation as the result of natural exposure.…”
Section: Downloaded Fromsupporting
confidence: 55%
“…In the present study, antigen-specific IFN-␥ levels decreased in the absence of transmission, but antigen-specific IL-10 levels also decreased in the absence of transmission. These findings are similar to those of a study we conducted in a different highland area of Kenya (4) but differ from studies we conducted in an area of malaria holoendemicity in Kenya (52) and in the same highland area as in the present study at two time points of much higher malaria incidence (53). In those studies, IL-10 levels did not differ significantly over time.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, the findings of some studies suggest that the breadth and magnitude of IFN- γ responses reduce quickly upon resolution of infection (John et al, 2004; Riley et al, 1993) leading to the suggestion that IFN- γ responses may be a marker of recent exposure. In contrast, repeat-cross-sectional studies in highland Kenya showed that IFN- γ responses to pre-erythrocytic antigens LSA-1 (John et al, 2000) and TRAP were stable over periods of very low malaria transmission (Moormann et al, 2009), possibly showing that IFN- γ responses may not be a good indicator of past exposure. Interestingly, a recent study suggested that IFN- γ responses to blood stage antigens are a marker of recent exposure but not protection, while IFN- γ responses to pre-erythrocytic antigen driven are associated with protection (Jagannathan et al, 2015).…”
Section: Introductionmentioning
confidence: 96%